Assembling Hexagonal‐Bipyramidal Mn8Zn2 and Mn8Zn4 Clusters. Issue 32 (5th September 2022) - Tziotzi, Thomais G.; Andreou, Evangelos K.; Mavromagoulos, Athanasios; Murrie, Mark; Dalgarno, Scott J.; Brechin, Euan K.; Milios, Constantinos J.
Abstract: Reaction between Mn(NO3 )2 ⋅ 6H2 O, Zn(NO3 )2 ⋅ 6H2 O, 1, 3, 5‐tri(2‐hydroxyethyl)‐1, 3, 5‐triazacyclohexane (H3 L) and pyrazole in MeOH under basic conditions leads to the formation of the decanuclear complex [Mn III 6 Mn II 2 Zn II 2 (L)2 (pyr)4 O4 (OH)4 (NO3 )2 (MeOH)2 (H2 O)4 ](NO3 )2 ⋅ Η2 Ο (1 ⋅ Η2 Ο). The metallic core of the cationic cluster consists of a central hexagonal‐bipyramidal Mn III 4 Mn II 2 Zn II 2 unit connected to two peripheral trivalent Mn centers arranged in a "trans" fashion, with one Mn III center lying above and one Mn III center below the hexagonal plane. Replacing Mn(NO3 )2 ⋅ 6H2 O with MnBr2 ⋅ 4H2 O and repeating the same reaction leads to the formation of the related, neutral decanuclear complex [Mn III 6 Mn II 2 Zn II 2 (L)2 (pyr)4 O4 (OH)4 Br4 (H2 O)2 ] (2 ), displaying the same metallic core as 1 . Addition of THF to the reaction mixture that produces (2 ) affords the neutral dodecanuclear complex [Mn III 6 Mn II 2 Zn II 4 (L)2 (pyr)6 O4 (OH)4 Br6 (H2 O)4 ] ⋅ 8THF (3 ⋅ 8THF), whose metallic skeleton retains the central hexagonal‐bipyramidal Mn III 4 Mn II 2 Zn II 2 unit found in 1 and 2 but is now connected to two peripheral Mn III Zn II units. Magnetic susceptibility and magnetization measurements carried out in the T =2–300 K temperature range and in fields up to B =7.0 T for all three complexes reveal dominant antiferromagnetic exchange interactions. Abstract : The use of the 1, 3, 5‐tri(2‐hydroxyethyl)‐1, 3, 5‐triazacyclohexane ligand in mixed‐metal manganese/zinc chemistry leads to the synthesis of three closely related complexes; two decanuclear Mn III 6 Mn II 2 Zn II 2 clusters and one dodecanuclear Mn III 6 Mn II 2 Zn II 4 cluster, all of which display similar structures based on a hexagonal‐bipyramidal Mn6 Zn2 central unit.